Costs of Smoking: Literature Review - Sarachitti, Rangsit; Polsiri, Piruna; Sithipongpanich, Thitima (Journal of Health Science of Thailand, 2017)
Not only does smoking cause harm to the smoker’s health, it also has a negative impact on surrounding people and the society. In addition, smoking causes significant losses to the country’s economy. There have been a large number of studies on smoking-attributable costs in many countries. The objective of this study is to review the literature on smoking costs in Thailand and other countries by gathering information from academic reports, journal articles and the World Health Organization. The results are categorized into three aspects: smoking-attributable costs, methods to analyze the smoking costs, and data and databases of smoking cost studies. Accordingly, the results of this research can be used as a guideline to study costs of smoking. Furthermore, this study is useful to academicians, policy makers and others who are interested in smoking, realted health and economic problems.